2021
DOI: 10.3928/01484834-20210322-09
|View full text |Cite
|
Sign up to set email alerts
|

Mock Oral Board Examination in Nurse Anesthesia Education

Abstract: Background: Despite its widespread use in anesthesia residency training, mock oral board examinations (MOBEs) are not included in the pedagogy of most nurse anesthesia programs (NAPs). A small-scale study was conducted to assess the use of MOBEs in this setting. Method: The investigational cohort consisted of 10 second-year students in a master's program in nurse anesthesia. MOBEs were scored according to a common rubric, and final scores were reconcile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…MOBEs employed with the two cohorts were nearly identical, with only minor modi cations, some of which were related to health and safety considerations stemming from the coronavirus disease of 2019 (COVID-19) pandemic. The MN cohort study has been previously reported [17]; therefore, the description of methods is limited, and methodological differences between the MN and DNP MOBE studies are highlighted.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…MOBEs employed with the two cohorts were nearly identical, with only minor modi cations, some of which were related to health and safety considerations stemming from the coronavirus disease of 2019 (COVID-19) pandemic. The MN cohort study has been previously reported [17]; therefore, the description of methods is limited, and methodological differences between the MN and DNP MOBE studies are highlighted.…”
Section: Methodsmentioning
confidence: 99%
“…By highlighting areas needing improvement, benchmark examinations are useful to de ne educational targets and objectives and allow discovery of approaches to ensure future excellence [25]. The MOBE used in this study originally was designed for precisely these purposes and successfully identi ed three areas of underperformance involving critical thinking in MN NAP students [17]. As a result, modi cations were implemented in the new DNP NAP curriculum designed to address these areas of performance, and the signi cantly improved performance of the current DNP cohort with MOBE likely represents a validation of its formative function.…”
Section: Mobe As a Benchmark Evaluation In Amentioning
confidence: 99%
See 2 more Smart Citations
“…13,14 Recently, an oral examination strategy modeled on the American Board of Anesthesiology Standardized Oral Examination (mock oral board examination or MOBE) 12 has been successfully employed for this purpose in a cohort of MN nurse anesthesia students. 15 As a result, oral examinations were added as a benchmark in this nurse anesthesia program's new DNP curriculum. This institution's use of oral examinations in both the previous MN and current DNP curricula offered a unique opportunity to compare outcomes related to the curricular change.…”
Section: Introductionmentioning
confidence: 99%